Roberte est-elle raciste ? Éclairer le déclassement du monde agricole provençal par la mémoire familial - Anne-Adélaïde Lascaux (Carnets de Géographes)
The Mediterranean agricultural world is a space in which xenophobic discourse is rife. While the Provençal huerta is a productive space based on the exploitation of a foreign seasonal workforce, the relations between employers and workers are complex. This paper proposes to revisit the manufacture of xenophobic discourse among Provençal farmers from the perspective of a particular position: that of a researcher, but also that of a country’s child, a daughter of local farmers and employers. The aim is to understand how different temporalities coexist in the field, between daily practices, childhood memories and the memory of ancestors. This temporal depth brings to the field a sensitive aspect allowing to recontextualize the construction of the employer's position in Provence in the light of the successive crises that the Mediterranean agricultural world has experienced, leading to a feeling of downgrading among farmers.